Commercial Banking - Gan, Christopher (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The existence of financial intermediaries is arguably an artifact of information asymmetry. Beyond simple financial transactions, financial intermediation provides a mechanism for information transmission, which can reduce the degree of information asymmetry and consequently increase market efficiency. During the process of information transmission, the bank is able to provide unique services in the production and exchange of information. Therefore, banks have comparative advantages in information production, transmission, and utilisation. This book provides an overview of commercial banking and includes empirical methods in banking such risk and bank performance, capital regulation, bank competition and foreign bank entry, bank regulation on bank performance, and capital adequacy and deposit insurance.